Monitoring of the Vertical Settlement In Heavy Structures By Precise Levelling - Hussein Alwan Mahdi (Journal of Engineering, 2023)
Monitoring and analysing of the vertical deformations or the settlements of the structures is one of the main research fields in geodetic applications, which is considered a precise periodic measurement, made at different epochs to investigate these deformations on heavy structures. In this research, the deformation measurements were carried out on one of Baghdad University buildings,” Building of Computers Department” of dimensions (70.0 * 81.3 m.). Due to some cracks observed in their walls, it was necessary to monitor the vertical displacement of this building at some particular monitoring points by constructing a vertical network and measured in different epochs. The first epoch (zero epoch) was carried out in April 2006, the second in July 2006, the third in October 2006 and the last one in October 2012. These four epochs include precise levelling measurements were adjusted by Least Squares Adjustment with the aim of investigating the settlement of this building. The two approaches “the Global Congruency test” and “the simple test” are carried out to detect if there any deformation. These two approaches were employed in the analysis and found the difference in elevations between two epochs most be ensured and found that if the monitoring points (P1 to P4) stayed really stable, when compared with the time interval or not?Then according to the analysis procedure to determine the localization of settlement at specific points in the case may change in elevation must be applied. The results showed in two different statistical techniques a significant settlement in four selected corner points on building (P1, P2, P3 and P4). The statistics are based on the probability 95% test and the congruency test with Fisher distribution table